IMPLEMENTASI LEARNING MANAGEMENT SYSTEM (LMS) DI LINGKUNGAN PENDIDIKAN TINGGI - Ningsih, Silvia; Suhardi, Muhamad; Sari, Indah Nurmala; Wulan, Dita Sri; Fadillah, M.; Amalia, Nadia (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2025)
ABSTRACT This study aims to analyze the implementation of Learning Management Systems (LMS) in higher education environments to support digital learning. LMS is an information technology-based platform that facilitates online learning processes in a structured, flexible, and well-documented manner. This study employs a descriptive quantitative method through a literature review approach, examining various research findings related to the effectiveness and challenges of LMS use in universities. The findings indicate that LMS has great potential to enhance learning effectiveness, encourage student engagement, and ease academic monitoring and evaluation. However, LMS implementation still faces several obstacles, such as low digital literacy among lecturers, limited technological infrastructure, and a lack of user readiness. This study emphasizes the importance of institutional support through training, academic system integration, and comprehensive digitalization policies to ensure optimal and sustainable utilization of LMS in addressing the challenges of 21st-century education. Therefore, the study highlights the need for strong commitment and support from higher education institutions in the form of systematic digital policy development, adequate infrastructure provision, integration of LMS with existing academic systems, and intensive training for both lecturers and students. ABSTRAK Penelitian ini bertujuan untuk menganalisis implementasi Learning Management System (LMS) di lingkungan pendidikan tinggi dalam mendukung pembelajaran digital. LMS merupakan platform berbasis teknologi informasi yang mampu memfasilitasi proses pembelajaran daring secara terstruktur, fleksibel, dan terdokumentasi. Studi ini menggunakan metode deskriptif kuantitatif melalui pendekatan studi literatur yang mengkaji berbagai hasil penelitian terkait efektivitas dan tantangan penggunaan LMS di perguruan tinggi. Hasil kajian menunjukkan bahwa LMS memiliki potensi besar dalam meningkatkan efektivitas pembelajaran, mendorong keterlibatan mahasiswa, serta memudahkan pemantauan dan evaluasi akademik. Namun demikian, implementasi LMS masih menghadapi hambatan seperti rendahnya literasi digital dosen, keterbatasan infrastruktur, dan kurangnya kesiapan pengguna. Penelitian ini menekankan pentingnya dukungan institusi melalui pelatihan, integrasi sistem akademik, serta kebijakan digitalisasi yang menyeluruh agar pemanfaatan LMS dapat optimal dan berkelanjutan dalam menjawab tantangan pendidikan abad ke-21, Oleh karena itu, penelitian ini menekankan pentingnya komitmen dan dukungan institusi pendidikan tinggi dalam bentuk penyusunan kebijakan digitalisasi yang sistematis, penyediaan infrastruktur yang memadai, integrasi LMS dengan sistem akademik yang ada, serta pelatihan intensif bagi dosen dan mahasiswa.